CRITICAL DISCOURSE ANALYSIS OF SARA MILLS' MODEL IN “THE PERFECT WIFE” - Yulianda, Asri; Ray, Sukma Adelina (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2025)
This study aims to critically analyze the gender ideology contained in the short story “Perfect Wife” by Aveus Har using Critical Discourse Analysis (CDA) Sara Mills Model. This short story was chosen because it explicitly challenges the ideal construction of the “perfect” role of a wife in a society that is steeped in patriarchal values. The method used is qualitative CDA with document analysis and close reading techniques, focusing on Mills's three discourse positions: Subject/Object Position, Writer Position, and Reader Position. The results of the study indicate the dominance of patriarchal ideology that is legitimized through language. The Subject/Object Position analysis reveals that the character of the Wife (who is ultimately revealed as a gynoid) is consistently positioned as a passive Functional Object, judged, and alienated from agency, making her a disposable commodity. In contrast, the character of the Husband is maintained as an Active Subject who has full authority in assessing and making decisions. Another key finding is the author's use of narrative irony. The plot twist of the wife as a robot serves as an ideological critique, suggesting that the demands of perfection on wives have reached an inhumanly absurd limit. The marital failure that occurs despite meeting the standards of perfection rhetorically shifts the focus of blame from the wife to the husband's imperfect expectations and oppressive patriarchal standards. The study's conclusion confirms that the discourse of the